Coping with COVID-19 using traditional medicine: perspectives from Joe Morolong, Northern Cape - Masego M. Motsumi; Livhuwani D. Nemakonde (Health SA Gesondheid: Journal of Interdisciplinary Health Sciences)
Background: Indigenous Knowledge Systems (IKS) have long been central to African communities, providing critical solutions to health and disaster challenges. Traditional medicine, a significant component of IKS, continues to play a vital role in addressing health needs, especially in rural areas.